(untitled) (CIPEEX, 2025)
Introduction: The skin, the largest organ of the human body, is composed of three layers, epidermis, dermis, and hypodermis, and performs essential protective and homeostatic functions. When injured, it triggers the wound-healing process, a dynamic and multifactorial sequence aimed at restoring tissue structure and function. This process is influenced by both local and systemic factors such as nutritional status, immune response, comorbidities, age, and pharmacological treatments. Historically, wound management has been described for more than five millennia, beginning with the use of natural substances and evolving with the advent of antisepsis, antibiotics, and surgical techniques. Today, a wide range of therapeutic resources is available, and analyzing the role of technological innovations is fundamental for guiding contemporary medical practice. Objective: To emphasize the technological advances applied to wound treatment and the healing process. Methods: An integrative literature review was conducted through searches in PubMed and SciELO. Only freely accessible full-text articles in Portuguese or English were included. The descriptors used were “Wound healing”, “Laser Therapy” and “Biotechnology”. Publications that did not meet these criteria or were unrelated to the central objective were excluded. Results: Wound healing may occur by primary, secondary, or tertiary intention, depending on the clinical and morphological characteristics of the lesion. Systemic conditions such as diabetes, malnutrition, or immunosuppression may delay repair and contribute to chronic wounds. Recent technological advances have broadened treatment options. Low-level laser therapy (LLLT) exerts biomodulatory effects by stimulating fibroblast activity, angiogenesis, and collagen synthesis. It has shown benefits in diabetic, venous, and pressure ulcers, including faster closure, pain reduction, and lower recurrence rates. Negative pressure wound therapy (NPWT) applies controlled subatmospheric pressure to the wound bed, reducing exudate, preventing edema and seroma, and promoting granulation tissue, particularly in complex wounds. Biological dressings, such as Nile tilapia skin and decellularized bovine peritoneum, mimic human skin properties and provide high collagen content, favoring re-epithelialization. Clinical evidence shows decreased pain, fewer dressing changes, shorter hospital stays, and better cosmetic outcomes compared with conventional therapies like Silver sulfadiazine. Hyperbaric oxygen therapy (HBOT) improves tissue oxygenation, stimulates angiogenesis, and reduces inflammation, proving effective in diabetic, vascular, and post-surgical wounds. Despite their promise, each modality has limitations and contraindications. LLLT must be cautiously considered in oncologic patients, while NPWT is contraindicated in wounds with exposed vessels or untreated necrosis. Hence, therapeutic decisions should be individualized and guided by multiprofessional evaluation. Conclusion: Wound healing is a complex, multifactorial process that combines historical foundations with modern advances. Effective management requires not only the rational use of innovative technologies but also an integrated, patient-centered, and multiprofessional approach. By aligning evidence-based practice with technological innovation, healthcare professionals can optimize healing, minimize complications, and enhance patient quality of life.